Influence of low temperature plasma oxynitriding on the mechanical behavior of NiTi shape memory alloys. (October 2018) - Witkowska, Justyna; Rudnicki, Jacek; Piekoszewski, Witold; Raugh, Gerhard; Morgiel, Jerzy; Wierzchoń, Tadeusz
Abstract: NiTi shape memory alloy was modified at low temperature plasma under glow discharge conditions in order to produce a TiO2 +TiN type diffusive surface layer. The paper presents the structure, chemical composition, surface topography and mechanical properties, such as hardness, reduced modulus and friction coefficient of NiTi alloy after proposed surface treatment in comparison to initial state. The oxynitriding process slightly increased the surface roughness and both hardness and elastic modulus. The friction coefficient was lowered independently of the friction path and load. Such results are promising in the context of increasing the wear resistance of NiTi alloy and designing its new industrial applications. Highlights: TiO2 +TiN type surface layer produced on NiTi shape memory alloy is presented. The oxynitriding process slightly increased the surface roughness of NiTi alloy. Both hardness and elastic modulus of surface layer was increased in comparison to NiTi core. The friction coefficient was lower for surface layer independently of the friction path and load. .